ECONOMIC ASPECTS OF THE USE OF FORESTRY PRODUCTS FOR COMMERCIAL PURPOSES - Marčeta, Milica; Keča, Ljiljana; Jelić, Sreten (Economics of Agriculture, 2024)
Forestry together with the industry based on wood and non-wood forest products (NWFPs) represents an important activity and branch of the national economy. In accordance with that, the work is divided into two chapters, one of which analyzes wood, and the other of NWFPs. Therefore, the aim of the research is to examine the market trends and potential of forestry in the part of central Serbia (Central forest area). The purpose of the research is to identify trends in the categories of felling, production and sale of wood assortments of beech, oak and poplar and to analyses the commercial aspect and the way of organizing the marketing mix in companies that deal with the purchase, processing and placement of NWFPs. The Mann-Kendall test was used for the analysis of trends in wood products, while a survey was created for the analysis of companies in the field of NWFPs, which included 29 open and closed questions, with conceptual units related to the marketing mix. For the purposes of the research, primary and secondary data were used and the time period 2008-2017 was covered.